Management Educational Information System During Pandemic Covid-19 Through Teachers’ Professionalism and Pedagogic - Dinar Roudhotul Lailia; Eni Fariyatul Fahyuni; Moch. Bahak Udin By Arifin (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
Management of education information systems is the management and utilization of information and communication technology (ICT) in education or e-Education. The management of the education information system has contributed to facilitating the tasks carried out by all teaching staff during the pandemic that occurred in Indonesia. This research is a quantitative study where this study aims to determine whether implementing education information system management on the professionalism and pedagogic competence of teachers in MI Muslimat NU Pucang and SD Muhammadiyah 1 Pucanganom Sidoarjo. In the process, this study conducted data collection techniques in questionnaires, interviews, and observations. Data management obtained from data collection results is managed using quantitative techniques through statistical test management using SPSS version 19. It is known from the results of the regression test from the analysis of the research results showing that the t value in the table is 1.993, for professional competence t count is 4.540 then ( 4,540> 1,993), and the pedagogic competence t count is 4,030 then (4,030> 1,993). So it concluded that Ho is rejected. It states that the education information system's management affects teachers' professionalism and pedagogic competence at MI Muslimat NU Pucang and SD Muhammaidyah 1 Pucanganom Sidoarjo